The effect of glucocorticoids on Thrombospondin‐1, Osteocalcin and the Thrombospondin‐1:Osteocalcin ratio in humans. (31st October 2019) - Cesana‐Nigro, Nicole; Keshvari, Sahar; Barclay, Johanna L.; Sorbello, Jane; Upham, John W.; Benham, Helen; Anderson, Stephen T.; Steiger, Natasha; Prins, Johannes B.; Inder, Warrick J.
Abstract: Objective: Thrombospondin‐1 (TSP1), a matricellular protein, and Osteocalcin (OCN), a noncollagenous protein secreted by osteoblasts, are known to be up‐ and down‐regulated, respectively, by glucocorticoids. The aim of this study was to determine whether a ratio between TSP1:OCN was altered by changes in glucocorticoid activity in humans. Design: Prospective observational study. Setting: Tertiary university hospital in Queensland, Australia. Patients and Measurements: Patients with Cushing's syndrome (CS, n = 19), asthma or giant cell arteritis on chronic prednisolone treatment (PRED, n = 13), adrenal insufficiency (AI, n = 16) and healthy volunteers (HV, n = 20). Plasma TSP1 and serum total OCN were measured by immunoassay at 0800h, 1200h and 1600h in patients with CS, patients with AI taking replacement glucocorticoids, HV before and after 4 mg dexamethasone and PRED patients predose at 800 and 4 hours post‐dose at 1200 hours. Results: Plasma TSP1 in CS was higher ( P < .0001), and serum OCN was lower ( P < .0001) than HV. The TSP1:OCN ratio in HV increased significantly after 4 mg dexamethasone ( P < .0001) and in AI after taking their hydrocortisone replacement therapy ( P < .001). PRED patients had a higher TSP1:OCN ratio compared with HV at both 800 and 1200 hours (both P < .001), but no significant change occurred from pre‐ to post‐dose. A TSP1:OCN ratio of >73 at 800 hours differentiated CS from HV with a sensitivity of 95% and a specificity of 100%. Conclusions: The TSP1:OCN ratio is elevated in patients on prednisolone and in patients with CS compared with healthy volunteers. It may be a useful biomarker of total body glucocorticoid activity in humans.